(untitled) (GYMNASIUM, 2017)
The blood tests represent the most precise currently used method, though not without certain traps. In this paper, we show some methods for blood testing, as well as other methods for estimating the training speeds, which require special equipment. The blood tests that determine the anaerobic threshold have something in common, since they measure the lactic acid concentration after each set of repetitions, when the intensity of the exercise is progressively increased. Our paper tries to answer the following questions: Do the methods of blood testing as well as other methods of estimating the exercise speeds represent a way of training the swimmers? Are the blood tests the optimal method used in the competitive swimming? Conclusions: We focused on the training of competitive swimmers because we consider there are a lot of people interested in getting the fundamental information about this age group, although most of coaches work with children.